Methodology Of Teachıng Isoprocesses Through Educatıonal Integratıon - Ergashev Jamshid Koldoshevich. (Genius Journals, 2024)
The article shows the process and result of achieving the integrity of the educational content through the establishment of integration between disciplines and interdisciplinary connections, interactions between different educational programs.
Keywords: Gases; gas; laws; integration; methodology